The role of physical and cognitive function in performance of activities of daily living in patients with mild-to-moderate Alzheimer’s disease – a cross-sectional study - Clemmensen, Frederikke K (BMC Geriatr, 2020)
BACKGROUND: Several factors may play a role in the ability of patients with Alzheimer’s disease to perform activities of daily living (ADL). The aim of this study was to examine the impact of different aspects of physical performance and cognitive functions on ADL in patients suffering from mild-to-moderate Alzheimer’s disease. METHODS: We conducted secondary analyses on cross-sectional baseline data from the randomized controlled multicentre study “Preserving quality of life, physical health and functional ability in Alzheimer’s Disease: The effect of physical exercise” (ADEX). In total, 185 AD patients (76 women and 109 men), with a mean age on 70,4 years, were included. Data from physical performance tests (Astrand cycle test, Timed up & Go (TUG), Sit to Stand test (STS)) and cognitive tests (Mini Mental Status Examination (MMSE), Symbol Digit Modalities Test (SDMT), Stroop Color and Word test (Stroop)) were used. Their associations with ADL, measured on the ADCS-ADL scale was assessed in multivariable regression analyses. RESULTS: SDMT and MMSE had significant, moderate correlations with total ADL (SDMT: r = 0.33, MMSE: r = 0.42) and instrumental ADL (SDMT: r = 0.31, MMSE: r = 0.42), but not with basic ADL. Adjusting for age and sex, the associations between SDMT and MMSE to total ADL and instrumental ADL persisted. No significant associations were found between Astrand, TUG, STS or Stroop and total ADL, basic ADL or instrumental ADL. CONCLUSION: Total ADL and instrumental ADL are associated with cognitive functions, including executive function. No significant association between examined physical performance parameters and ADL functions was observed, and consequently does not support an impact of physical function on ADL functions in patients with mild-to-moderate Alzheimer’s disease and relatively well-preserved physical function. Strategies aimed to improve cognition may be better suited to improve ADL function in patients with mild-to-moderate Alzheimer’s disease. TRIAL REGISTRATION: NCT01681602. Registered 10 September 2012, retrospectively registered.